2014
DOI: 10.1136/oemed-2014-102286
|View full text |Cite
|
Sign up to set email alerts
|

CAREX Canada: an enhanced model for assessing occupational carcinogen exposure

Abstract: ObjectivesTo estimate the numbers of workers exposed to known and suspected occupational carcinogens in Canada, building on the methods of CARcinogen EXposure (CAREX) projects in the European Union (EU).MethodsCAREX Canada consists of estimates of the prevalence and level of exposure to occupational carcinogens. CAREX Canada includes occupational agents evaluated by the International Agency for Research on Cancer as known, probable or possible human carcinogens that were present and feasible to assess in Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 13 publications
2
76
1
Order By: Relevance
“…The work carried out by Peters et al 7 reported in this issue and that by others, for example Carey et al 12 in a previous issue in this journal, is therefore very important. There are clearly limitations to any approach that aims to develop such estimates, as acknowledged by Peters et al , and further efforts should be encouraged to improve the accuracy of the estimates and to track any temporal changes in the prevalence as well as intensity of exposure.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…The work carried out by Peters et al 7 reported in this issue and that by others, for example Carey et al 12 in a previous issue in this journal, is therefore very important. There are clearly limitations to any approach that aims to develop such estimates, as acknowledged by Peters et al , and further efforts should be encouraged to improve the accuracy of the estimates and to track any temporal changes in the prevalence as well as intensity of exposure.…”
mentioning
confidence: 84%
“…However, estimates provided by Peters et al 7 for Canada, as well as by Carey et al 12 for Australia and by us for Britain13 and the EU14 show that the prevalence of exposure to carcinogens is still high in certain industries, in particular for respirable crystalline silica, diesel exhaust fumes, ultraviolet radiation and shift work.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…This evidence came mainly from workers in the railroad, trucking and mining industries, where the use of diesel engines is widespread. Millions of workers around the world are exposed to diesel exhaust,2 and in Canada, it is the most prevalent occupational lung carcinogen 3. Lung cancer is the most commonly diagnosed cancer as well as the leading cause of death from cancer in Canada,4 5 therefore the public health impact of occupational DEE exposure may be considerable.…”
Section: Introductionmentioning
confidence: 99%